Long-Term Care medicines formularies: any reasons for pharmacists’ concern? - Rafael Gonçalves, João (2023)
This study aimed to characterize and compare medicines formularies (MFs) used in Long-Term Care (LTC) facilities in Portugal, and to identify the prevalence of Potentially Inappropriate Medicines (PIMs). A systematic contact with LTC facilities was undertaken in December 2021. MFs were systematized according to the Anatomical Therapeutical Chemical classification system (ATC), followed by descriptive content analysis. A structured comparison between MFs developed by public organizations and private LTC facilities was performed. After duplicate removal and exclusion of medicines not for systemic use, two explicit criteria - the Algorithm of medication review in frail older people and the EU(7)-PIM list - were employed for PIMs identification. Five MFs were obtained and assessed. The three MFs developed by private institutions covered 23% of the national LTC facilities and approximately 34% of the national total of beds. Heterogeneity was particularly high for the Alimentary tract and metabolism, Blood and blood-forming organs, Musculoskeletal system, and Respiratory system ATC groups. A PIM prevalence of 29,4% was identified. Medicines distribution between the MFs suggests the need to develop national guidelines towards harmonizing medicines usage in LTC. The prevalence of PIMs found highlights the importance of a particular optimized use of this health technology in aged sub-populations.